TIME TOKEN TECHNIQUE TO IMPROVE THE STUDENTS’ LEARNING ACTIVITY AND COMMUNICATIVE COMPETENCE - Bambang - Susatyo (Universitas Muria Kudus, 2021)
ABSTRACT The purpose of this research is to know the effectiveness of Cooperative Learning Time Token towards student’s learning activity and Communicative Competence in speaking English. This research uses Classroom Action Research procedures. The research consists of two cycles, each comprises four phases, namely planning, acting, observing and reflecting. The subject of the research is the students of SMK N 2 Temanggung semester 1 2019/2020. To get data, the writer uses Brown’s Scale of Test of Spoken English. While for students’ activities, the writer uses a set of observation sheet to observe the activity of the students in class. The research reveals that the uses of Time Token technique in English class has increased the students’ Learning activities from 68 % in Pre-cycle to 78% in cycle 1 and 80 % in cycle 2. The Communicative competence in speaking English has increased from 74 to 78 in cycle 1 and 81 in cycle 2Key words : Time Token, students’ activity and students’ communicative competence